Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper, 2006)
Since its April 2006 Report, the IEO has continued work on three ongoing evaluations. It has considered and discussed a broad list of possible future evaluations with a wide range of stakeholders and announced its decision to add four of these to the IEO work program in the financial year 2007. IEO has also started to follow up on the recommendations of the report of the independent external evaluation of the IEO.